Economic-environmental theories and their link with the social dimension of sustainability in Protected Natural Areas - Ávila-López, Cielo María (Universidad Autónoma de Tamaulipas, 2018)
Protected Natural Areas (PNA) are considered instruments to conserve biodiversity and achieve sustainable development. However, its establishment generates inconveniences due to the exclusion of the interests and needs of the populations (social dimension), which hinders such development. The objective of this work was to determine which of the main economic-environmental theories addresses the social dimension of sustainable development and therefore, problems in PNA, which involve its inhabitants. For this, a review of the state of the art of the theories was carried out: environmental economics, natural resources economics, green economy and ecological economics, identifying the characters of each one, its relationship with sustainability and with the policies promoted by each of them. Our review indicates that the ecological economy theory is adequate to address the inclusion of the human factor in the PNA, since it considers the perspectives of the communities and listens to their interests and needs, regarding the use of natural resources.